Faktor yang Mendorong Intensi untuk Melanjutkan Penggunaan Dompet Digital: Studi Pada Pengguna di Pulau Jawa - Budirahardjo, Mario; Laksmidewi, Dwinita (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The tight competition in the e-wallet market and the rapid growth in the number of users in Indonesia require e-wallet companies to retain their users. This study aims to analyze the direct and indirect effects perceived security, trust in mobile payment, perceived usefulness, perceived enjoyment, user interface on user’s continuance intention to use e-wallet. The type of data in this research is primary data, with an online survey method using google form, and the sample technique is purposive sampling, involving 350 respondents who live in Java and for the last 1 month have used one of the GoPay, OVO, DANA, or ShopeePay. Data analysis using Structural Equation Model. The results show that perceived security, trust in mobile payments, user interface can not directly affect the user's continuance intention to use e-wallet. Meanwhile, perceived usefulness and perceived enjoyment have direct effect on continuance intention to use. The results of the indirect effect proved that satisfaction can mediate the influence of trust in mobile payment, perceived usefulness, perceived enjoyment, user interface on user’s continuance intention to use e-wallet. However, satisfaction was not able to mediate the effect of user's perceived security on continuance intention to use. Keywords: perceived usability, perceived security, trust in mobile payment, satisfaction, continuance intention to use